2022
DOI: 10.1200/jco.2022.40.16_suppl.9041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of the BAT1706 (proposed bevacizumab biosimilar) compared with reference bevacizumab in patients with advanced nonsquamous NSCLC: A randomized, double-blind, phase III study.

Abstract: 9041 Background: A Randomized, Double-blind, Phase III Study was conducted to confirm clinical similarity between BAT1706, a proposed biosimilar to reference bevacizumab, and EU-bevacizumab in patients with advanced non-squamous non-small cell lung cancer (NSCLC). Methods: Patients were randomized 1:1 to BAT1706 plus paclitaxel and carboplatin (Arm A) or EU-bevacizumab plus paclitaxel and carboplatin (Arm B) given three weeks for 6 cycles, followed by maintenance therapy with BAT1706 or EU- bevacizumab. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In a Phase I trial in healthy volunteers, BAT1706 was shown to be highly similar to EU/US-bevacizumab in terms of PK equivalence (90% CI for the AUC 0–inf was 99–112% for BAT1706 versus EU-bevacizumab and 97–110% for BAT1706 vs US-bevacizumab), safety (no significant adverse events attributable to BAT1706, as compared to EU/US-bevacizumab), and immunogenicity (no anti-drug antibody positive result was reported for any subject) [ 19 ]. BAT1706 has also been evaluated in a Phase III trial in patients with advanced nonsquamous non-small-cell lung carcinoma, where clinical equivalence to EU-bevacizumab was demonstrated in terms of efficacy (48% patients achieving overall response rate in BAT1706 arm and 44.5% in EU-bevacizumab arm; progression-free survival at 12 months was 20.7% and 21.8%, respectively), safety (incidence of treatment-emergent adverse events [TEAEs] and study drug-related TEAEs was similar between BAT1706 and EU-bevacizumab arms), PK (mean serum concentrations were comparable between BAT1706 and EU-bevacizumab), and immunogenicity (no positive neutralizing anti-drug antibodies in any patient) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Phase I trial in healthy volunteers, BAT1706 was shown to be highly similar to EU/US-bevacizumab in terms of PK equivalence (90% CI for the AUC 0–inf was 99–112% for BAT1706 versus EU-bevacizumab and 97–110% for BAT1706 vs US-bevacizumab), safety (no significant adverse events attributable to BAT1706, as compared to EU/US-bevacizumab), and immunogenicity (no anti-drug antibody positive result was reported for any subject) [ 19 ]. BAT1706 has also been evaluated in a Phase III trial in patients with advanced nonsquamous non-small-cell lung carcinoma, where clinical equivalence to EU-bevacizumab was demonstrated in terms of efficacy (48% patients achieving overall response rate in BAT1706 arm and 44.5% in EU-bevacizumab arm; progression-free survival at 12 months was 20.7% and 21.8%, respectively), safety (incidence of treatment-emergent adverse events [TEAEs] and study drug-related TEAEs was similar between BAT1706 and EU-bevacizumab arms), PK (mean serum concentrations were comparable between BAT1706 and EU-bevacizumab), and immunogenicity (no positive neutralizing anti-drug antibodies in any patient) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…were uncertain risk, 37,41,44,52,62 and 2 (5.1%) were high risk. 56,61 Of the cohort studies, 4 (40.0%)…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…Of those, 37 RCTs were published in journals, 32-35,37-50,52-70 1 was reported in ClinicalTrials.gov, 51 and 1 was reported in an NMPA review. 36 Of the 39 RCTs, 18 studied bevacizumab biosimilars, [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] 12 studied rituximab biosimilars, 50-61 and 9 studied trastuzumab biosimilars. [62][63][64][65][66][67][68][69][70] Of the RCTs, 33 were prespecified as equivalence designs, [32][33][34][35][36][37][38][39][40][41][42][43][44][46][47][48][49][50][51][52][53][54][55]58,60,…”
Section: Rct and Cohort Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations